2002
DOI: 10.1093/brain/awf108
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation and sexual arousal in healthy, heterosexual males

Abstract: Despite the brain's central role in sexual function, little is known about relationships between brain activation and sexual response. In this study, we employed functional MRI (fMRI) to examine relationships between brain activation and sexual arousal in a group of young, healthy, heterosexual males. Each subject was exposed to two sequences of video material consisting of explicitly erotic (E), relaxing (R) and sports (S) segments in an unpredictable order. Data on penile turgidity was collected using a cust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
266
0
10

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(308 citation statements)
references
References 50 publications
24
266
0
10
Order By: Relevance
“…This suggests that paroxetine may lead to an impaired responsiveness of brain regions previously ascribed to the processing of emotional and autonomic functions that are associated with but also reach beyond the pure autonomic triggering of sexual arousal. Our observation that activation of the hypothalamus as a key autonomic component of sexual arousal (Arnow et al, 2002;Ferretti et al, 2005) did not show an effect of medication at the predefined statistical thresholds might be in line with this claim, although interpretation of this null result should be treated with caution.…”
Section: Blunted Anterior Cingulate Activation Under Paroxetinesupporting
confidence: 63%
See 1 more Smart Citation
“…This suggests that paroxetine may lead to an impaired responsiveness of brain regions previously ascribed to the processing of emotional and autonomic functions that are associated with but also reach beyond the pure autonomic triggering of sexual arousal. Our observation that activation of the hypothalamus as a key autonomic component of sexual arousal (Arnow et al, 2002;Ferretti et al, 2005) did not show an effect of medication at the predefined statistical thresholds might be in line with this claim, although interpretation of this null result should be treated with caution.…”
Section: Blunted Anterior Cingulate Activation Under Paroxetinesupporting
confidence: 63%
“…Stimulation with erotic video clips has already been demonstrated as a reliable tool to investigate brain regions related to sexual functioning (Redoute et al, 2000) and to contrast medication effects on these brain regions in patients suffering from depression (Kim et al, 2009). Under placebo, we expected to find activation in those brain regions that are reported to be active during erotic stimulation according to previous fMRI studies, that is, the anterior cingulate cortex (ACC), lateral occipital cortex, insula, amygdala, hypothalamus, thalamus, and the ventral striatum (Arnow et al, 2002;Ferretti et al, 2005;Moulier et al, 2006;Mouras, 2004;Redoute et al, 2000;Walter et al, 2008a, b). In line with previous studies of blunted ventral striatal activation under SSRIs (McCabe et al, 2010), paroxetine was expected to exert inhibitory effects on reward system activation, the latter being identified as specifically elicited by erotic stimulation as a primary reward (Walter et al, 2008a).…”
Section: Introductionmentioning
confidence: 98%
“…1 Using these techniques, when sexually stimulated, the activation of the right subinsular/insula region including the claustrum has been demonstrated using both fMRI and PET scanning techniques. 2 Other brain regions that have been reported to be activated during visual sexual stimuli include the right middle gyrus, right temporal gyrus, left caudate and putamen, bilateral cingulate gyri, right sensimotor and pre-motor regions. 1 Other studies have shown activation of the cerebellum in response to visual erotic stimuli as well as viewing pictures of sexual partners.…”
Section: Neuroanatomy Of Male Sexual Responsementioning
confidence: 99%
“…These results are in agreement with other reports in literature of visually evoked sexual arousal in males showing bilateral activation of prefrontal areas, parietal lobes and, mainly, the occipital and inferior temporal, vision related, regions. [15][16][17][24][25] It has been proposed that human sexual arousal is a multifactor process comprising inter-related components. Among these there are the cognitive, emotional, motivational and physiological components, which concern different and specific cortical and …”
Section: Brain Modulation During Sexual Stimulation: Ed F Montorsi Et Almentioning
confidence: 99%